Species of Blepharicera Macquart from China with descriptions of two new species (Diptera: Blephariceridae) - Kang, Zehui; Yang, Ding (Zootaxa, 2014)
Blepharicera asiatica (Brodsky, 1930) is newly recorded from China. Two species, Blepharicera hainana sp. nov. and B. hebeiensis sp. nov., are described as new to science. A key to the known species of the genus Blepharicera from China is presented.